Electric Field Analysis and Experimental Study of Hybrid Lightning Protective Equipments - Kim, Young-Sun; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: Lightning phenomena are increasing in frequency and intensity as industrial society develops. Therefore, each country enacts regulations and laws in consideration of environmental factors such as climate and topography and cultural factors.Methods/Statistical analysis: Â We propose a hybrid method that combines two types of lightning protection facilities. The hybrid method is to protect the facility by installing a horizontal conductor in the ridge of the building and applying a leading streamer type lightning rod in the center.Findings: Through testing and numerical analysis, the hybrid method showed excellent protection efficiency and economical efficiency. The electric field analysis was performed by comparing the horizontal conductor method, the lightning rod method and the HEC method, and the discharge current was measured and verified through experiments.Improvements/Applications: The HEC method can be effectively applied to the lightning protection of modern buildings if it is used in parallel with the grounding equipment.Â Â
Keywords: Horizontal conductor; Hybrid method; Lightning protection; Lightning rod; Steamer.